As arritmias ventriculares na Doença de Chagas não são fenômenos aleatórios: estudo sobre a determinação do índice de previsibilidade através da monitorização de longo prazo - Silva, Nancy Christiane Ferreira [UNIFESP] (2016)
Background: The variability of ventricular arrhythmias among days of week in patients with Chagas disease is not detected by 24 hours of Holter monitoring. Objective: To analyze whether these arrhythmias are a random phenomenon or have some predictable pattern suggestive of long-term memory effect and reproducible behavior in patients with Chagas cardiomyopathy. Methods: Daily Holter monitoring was recorded in 16 subjects with mean age of 52±8 years. They were clinically stable and without signs of heart failure. The arrhythmic episodes analyzed during the days of monitoring were ventricular couplets, isolated premature ventricular contractions (PVCs), and non-sustained ventricular tachycardia (NSVT). The recording occurred during seven consecutive days for each patient, totaling 98 hours of monitoring. Each recording days was compared among themselves from the first until the seventh and last day. Statistical analysis: Considering the data format when presented in graphic of time series and to prove whether a phenomenon is or is not random, we choose the Hurst method (Hurst Exponent - H) to analyze the data. Result of H > 0.5 and ? 1 would imply in non- random phenomenon and possible long-term memory effect. It was also estimated the Fractal Dimension (D) and the Predictability Index (PI) of these events. To compare the incidence and variability of those events among days of the week, we analyzed the arrhythmic findings by the ANOVA with Repeated Measures. Results: The Hurst Exponent was significant > 0.5 in all 16 patients, which confirm the non-randomness of these arrhythmias in this Chagas? sample. The predictability index for ventricular couplets and isolated PVCs were on average 38% and 54%, respectively. ANOVA with measure repeated showed significant differences on daily frequency and expression pattern of ventricular couplets (n = 15, p ? 0.05), Isolated PVC (n = 12, p ? 0.05) and NSVT (n = 7, p ? 0.05). Conclusion: Ventricular arrhythmias in Chagas cardiomyopathy are not random phenomena but possibly long-term memory expression of cardiac cells. The arrhythmic occurrences in these patients showed no similarity among days in the analyzed period. Alternatively, it was detected large variations in the frequency and type of arrhythmias, making it unlikely that 24 hours of Holter recording may capture the variability of this phenomenon.